Modified frailty index predicts postoperative outcomes of Chinese elderly patients undergoing transforaminal lumbar interbody fusion - Yuhang Ma; Qiqi Wei; Xinglei Ben; Xiaozhong Zhou; Kelv Shen; Jiaming Qian; Yanming Hao; Zhengfeng Lu (Journal of Orthopaedic Surgery and Research)
Abstract Objective To evaluate the value of modified frailty index in the perioperative risk assessment of elderly patients undergoing transforaminal lumber interbody fusion(TLIF)surgery. Methods The clinical data of elderly patients who underwent TLIF surgery in our hospital from January 2018 to August 2023 were retrospectively analyzed. An 11-factor modified frailty index (mFI) was used to evaluate the health status of the patients. T-test, χ² test and logistic regression analysis were used to evaluate the correlation between mFI and perioperative risk and postoperative outcome variables. Receiver operator characteristic (ROC) curve was drawn, and age, American Society of Anesthesiology (ASA) and BMI were adjusted to evaluate the prediction effect of mFI on perioperative risk. Results A total of 254 patients were included, and they were divided into four groups according to mFI values: mFI = 0, mFI = 0.09, mFI = 0.18 and mFI ≥ 0.27. When the mFI increased from 0 to 0.27, the probability of having at least one complication increased from 10.3 to 44.0%. Multivariate logistic regression analysis showed that mFI ≥ 0.27 was an important risk factor for postoperative complications (OR = 6.81, 95%CI: 1.90-24.47, P < 0.05), pulmonary complications (OR = 8.07, 95%CI: 1.02–63.70, P < 0.05) and wound complication (OR = 9.33, 95%CI: 1.19–73.31, P < 0.05).The AREA under the ROC curve of perioperative risk predicted by the mFI model was 0.685, which had a significant advantage than the evaluation indexes such as age, ASA and BMI (P < 0.05). Conclusions The modified frailty index (mFI) is an effective indicator for assessing perioperative risk in elderly patients undergoing TLIF surgery, providing clinicians with a simple, objective, and repeatable mechanism for assessing frailty in elderly patients. In this way, patients can be classified and evaluated preoperatively, and preoperative management can be adjusted to reduce perioperative risk and develop a more appropriate treatment plan.